Nutritional evaluation of three species of fodder trees: Morus alba, Gliricidia sepium and Trichanthera gigantea in fistulated cattle (Revista Sistemas de Producción Agroecológicos, 2014)
This experiment was carried out on the farm and in the laboratory of Animal Nutrition and Food of the University of the Llanos, located in Villavicencio (Meta), three heifers Brown Swiss-Creole, fistulated rumen were used, which were fed Brachiaria decumbens, mineralized salt and water ad libitum also supplemented with 2 kg dry matter of three species of tree fodder thus forming three treatments: T1 = Morus alba, T2 = Trichanthera gigantea and T3 = Gliricidia sepium, to ensure consumption 300 gr of molasses were added at the time of delivery. The forages were evaluated in the laboratory by proximal analysis and determination of neutral detergent fiber (NDF) and acid detergent fiber (ADF). Field three experimental periods using a Latin square experimental design 3 x 3 in order to determine the ruminal degradability and degradation rate, using the technique of the nylon bags were developed, in which were placed 5 gr of sample from each treatment at different times (6, 12, 24, 48 and 72). Nutrients assessed were: dry matter (DM), NDF, ADF and total nitrogen (TN). In ruminal pH measurements and liquid ammonia nitrogen (N-NH3) at 0, 4, 8 and 12 hours were performed. The results of the compositional analysis indicated that Gliricidia sepium contains more protein (22.1%) compared with Morus alba and Trichanthera gigantea (18.6 and 19.2% respectively). Morus alba contains only 28.3% FDN in relation to the other two species whose value exceeds 40%, also had the highest rates of degradation as DM, TN, ADF and NDF (P
Keywords: Morus alba; Trichanthera gigantea; Gliricidia sepium; ruminal degradability